An unusual case of labial fusion in a post pubertal girl - Amin, Kinnari; Kadikar, Bhamini; Rajput, Heena; Patel, Krupa; Shah, Nilesh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Labial fusion is defined as either partial or complete adherence of the labia minora. It is also known as vulvar fusion, labial adhesion, labial agglutination or synechia of the vulva. This condition is common in pre-pubertal girls when estrogen levels are low and commonly resolves spontaneously post-puberty. This condition is usually asymptomatic and can be treated with topical application of estrogen or betamethasone cream or by manual or surgical separation of adhesions. We present a case of labial fusion in post pubertal girl which was managed surgically.